Collaborative Leadership: Cultivating an Environment for Success - Calvert, Kristin (2018)
This paper details the importance (and limitations) of leadership to foster an environment that supports collaboration in library acquisitions. The conditions necessary to create successful teams are examined:creating a compelling vision, enabling effective communication, and building trust among participants. The challenges of effective leadership grow in more complex collaborative endeavors, when there are mismatched priorities, or when leading teams outside of traditional reporting structures. This paper offers guidance for navigating these pain points to produce better and more inclusive processes.--This article has been published in Collaborative Librarianship, Vol. 10, Iss. 2, Article no. 4